2020
DOI: 10.1111/bcp.14203
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions on the appropriate use of opioids for noncancer pain among hospital inpatients: A systematic review

Abstract: Aims To summarise the effectiveness of interventions on appropriate opioid use for noncancer pain among hospital inpatients. Methods Two reviewers independently searched 6 databases up to March 2018 original research articles reporting on quantitative outcomes of interventions on appropriate opioid use among hospital inpatients. Appropriate opioid use was measured by changes in prescribing, such as the lowest effective opioid dose and duration, or clinical outcomes such as adequate pain control. Quality and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
17
0
Order By: Relevance
“…Delivering an academic detailing program to small groups of clinicians by pharmacists could increase the likelihood of prescribers following the pharmacists’ recommendations in the EHR (Bos et al., 2017; Soumerai & Avorn, 1990). Liu et al already concluded that interventions involving academic detailing show positive effects on appropriate opioid prescribing and clinical outcomes related to opioid use among inpatients (Liu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delivering an academic detailing program to small groups of clinicians by pharmacists could increase the likelihood of prescribers following the pharmacists’ recommendations in the EHR (Bos et al., 2017; Soumerai & Avorn, 1990). Liu et al already concluded that interventions involving academic detailing show positive effects on appropriate opioid prescribing and clinical outcomes related to opioid use among inpatients (Liu et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the main cause of preventable drug‐related admissions for opioids were the occurrence of ADEs (including constipation, nausea, sedation and respiratory depression) and overtreatment (Howard et al., 2007). Recent evidence has suggested that a significant proportion of opioids prescribed during hospital admission are continued post‐discharge, which may contribute to an increased risk of dependence and additional harm (Liu et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the size of the study may also provide a more in-depth look at the results found, such as the impact of study participants and pharmacists demographics on outcome measures (e.g., psychological factors, pharmacy experience, level of knowledge, etc.) [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several reviews have assessed interventions used to improve appropriate opioid prescribing. 14 , 15 In 2019, Asamoah-Boaheng et al conducted a systematic review and meta-analysis related to strategies on opioid prescribing for non-cancer pain, including the influence of education, audit, and feedback, interprofessional support, shared decision-making and reported that it was challenging to make conclusions about the effectiveness of such approaches because studies varied in study design and generally were of low methodologic quality. 14 A 2020 systematic review by Liu et al examined the effectiveness of AD and other interventions on opioid prescribing for non-cancer pain in an inpatient setting and reported that whilst the quality of evidence was low, AD and education followed by feedback increased appropriate opioid prescribing in agreement with guidelines.…”
Section: Introductionmentioning
confidence: 99%